A Content Analysis of Speaking Tasks in English Textbook “English for Nusantara” for Junior High School - Ega Safira; Ratna Dewi; Nunung Anugrawati (Universitas Islam Negeri Palopo, 2025)
This study aimed to find out the cognitive process dimensions and the arrangement of chapter 1,2,3,4, and 5 of speaking tasks in the “English for Nusantara” textbook for Junior High School. This study employed a content analysis method with a qualitative approach based on Revised Bloom’s Taxonomy, determining the extent to which the textbook promotes students' cognitive skill development in speaking English. The object of study is chapter 1,2,3,4, and 5 of speaking section in English for Nusantara Textbook. The data obtained through twelve of tasks in speaking sections. The findings revealed that the speaking tasks have five cognitive process categories: remembering (C1), understanding (C2), applying (C3), analyzing (C4) and creating (C6). However, the only categories evaluating (C5) were not found in the analyzed tasks. Additionally, the arrangement of tasks is sequence, which is in this book followed a progression from Lower-Order Thinking Skills (LOTS) to Higher-Order Thinking Skills (HOTS). It is suitable for EFL learning because the pattern in English for Nusantara is designed to develop students' thinking skills step by step. However, there are still gaps in covering more complex cognitive categories, indicating a need for further improvements to ensure that students receive a more comprehensive learning experience. Therefore, the conclusion was the speaking tasks in English for Nusantara textbook for Junior High School published by Ministry of Education and Culture was categorized as LOTS level.